PENGARUH KUALITAS AUDIT DAN UKURAN KOMITE AUDIT TERHADAP MANAJEMEN LABA (Studi Empiris pada Perusahaan Manufaktur di Bursa Efek Indonesia (BEI)) - Sunandar Sunandar; Ida Farida; M Alfin (Universitas Peradaban, 2014)
This research aims to analyze and provide empirical evidence of the effect of audit quality and audit committee size on earnings management. The size of the accounting public firm and industry specialist auditors are used to proxy the audit quality. Modified Jones Model is used to calculate discretionary accruals (a proxy or earnings management). This study uses secondary data derived from the Indonesian Capital Market Directory (ICMD) and the financial statements of companies listed in Indonesia Stock Exchange in 2010-2011. This study used a purposive sampling method and can 168 companies. Methods of analysis of this study use multiple regressions with SPSS. The results of the study indicate that the size of the firm, industry specialist auditors, and audit committee size proved to have no effect on earnings management.